Proteome-Wide Alterations of Asymmetric Arginine Dimethylation Associated With Pancreatic Ductal Adenocarcinoma Pathogenesis - Wei, Meijin; Tan, Chaochao; Tang, Zhouqin; Lian, Yingying; Huang, Ying; Chen, Yi; Chen, Congwei; Zhou, Wen; Cai, Tao; Hu, Jiliang (Frontiers in Cell and Developmental Biology, 2020)
Arginine methylation catalyzed by PRMTs (protein arginine methyltransferases) performs essential roles in regulating cancer initiation and progression, but its implication in PDAC (Pancreatic ductal adenocarcinoma) remains poorly elucidated. In this study, ADMA (asymmetric dimethylarginine)-containing peptides in PDAC cell line PANC-1 were identified by label-free quantitative proteomics combined with affinity purification, using human noncancerous pancreatic ductal epithelium cell line HPDE6c7 as the control. Totally 289 ADMA sites in 201 proteins were identified in HPDE6c7 and PANC-1 cells, including 82 sites with lower dimethylation and 37 sites with higher dimethylation in PANC-1 cells compared with HPDE6c7 cells. These ADMA-containing peptides demonstrated significantly enrichment of glycine and proline residues in both cell lines. Importantly, leucine residues were significantly enriched in ADMA-containing peptides identified only in HPDE6c7 cells or showing lower dimethylation in PANC-1 cells. ADMA-containing proteins were significantly enriched in multiple biological processes and signaling cascades associated with cancer development, such as spliceosome machinery, the Wnt/-catenin, Hedgehog, TGF- (tumor growth factor beta) and MAPK (mitogen-activated protein kinase) signaling pathways. Moreover, PDAC cell lines with enhanced cell viability showed lower PRMT4 protein abundance and global ADMA-containing protein levels compared with HPDE6c7. PRMT4 overexpression partially recovered ADMA-containing protein levels and repressed viability in PANC-1 cells. These results revealed significantly altered ADMA-containing protein profiles in human pancreatic carcinoma cells, which provided a basis for elucidating the pathogenic roles of PRMT-mediated protein methylation in pancreatic cancer.